A functional approach to group work in occupational therapy - Howe, Margot C., ....-; Schwartzberg, Sharan L., ....- (Philadelphia : Lippincott, Williams and Wilkins, 2001)
Contents: --------- I. GROUP WORK AND THE FUNCTIONAL GROUP MODEL 1. The group 2. History of occupational therapy group treatment 3. Group Practice in the Wellness Era 4. A model for group work II. LEADERSHIP AND FOUR STAGES OF THE FUNCTIONAL GROUP 5. Role of the leader in the functional group 6. Stage one: design 7. Stage two: formation 8. Stage three: development 9. Stage four: termination III. TEACHING AND RESEARCH 10. Concluding remarks: teaching and research
Keywords: Groepswerk -- Ergotherapie; Groepswerk